User features and gendered patterns in repeat online advice-seeking behavior - Bianca Kang; Moon-Ho Ringo Ho; Kokil Jaidka (Journal of Quantitative Description: Digital Media)
There is limited understanding of the user-level variables related to the common activity of repeat advice-seeking on virtual communities. Gender is of particular interest; past studies indicate men participate less on support forums. Social role theory provides descriptions of the interplay between gender roles and help-seeking, but these have not been quantified in an online context. We conduct a computational linguistic analysis on a year-long dataset of 17896 users on Reddit’s r/relationships, comparing the demographics, linguistic choices, and user histories of repeat and non-repeat advice-seekers self-identifying as male or female. We find strong evidence of gendered behavior, with users largely behaving more similarly to their identified gender. Female users are more likely to be repeat advice-seekers and to engage in advice-giving alongside their future advice-seeking attempts. There are otherwise no significant differences between the proportions of male and female users who return solely to seek advice. Female users are also more likely to write longer and more informally, seeking advice on domestic issues and communication. Male users are more focused on dating and past partners. Our findings shed light on the characteristics of a possibly vulnerable user population and set the foundation for future investigations on the influence of offline social roles on online help-seeking.